Gambaran Jumlah Platelet pada Anak dengan Diagnosa Demam Berdarah Hari Ketiga Sampai Hari Kelima - Wina Apriliani Rahayu; Agus Sudrajat (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Dengue Hemorrhagic Fever (Dengue Fever) is a type of infectious disease caused by the Arthoda virus, genus Flavivirus, family Flaviviridae. Platelets can decrease because the bone marrow experiences a decrease in platelet production, one of which is caused by the dengue hemorrhagic fever virus. Platelets are formed in the bone marrow through the fragmentation of the cytoplasm of megakaryocytes. The bite of the Aedes mosquito is a spreader of the dengue virus. The normal platelet count is 150,000 – 400,000mm3 and platelets have a normal lifespan of 7-10 days. This study aims to determine platelet levels from the third to the fifth day in dengue patients. The type of quantitative descriptive research uses a cross-sectional approach method. It was carried out at Hermina Arcamanik Hospital. The population of this study consists of all dengue hemorrhagic fever patients with a random sample of 30 people taken in March-April 2024 (random sampling). The results of the study based on age group showed that the majority of dengue patients were ≤ 5 years old, namely 13 respondents (46.4%). Based on gender, the most males were 18 people (64.3%).